If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 4) = 4 + n Reorder the terms: 3(4 + n) = 4 + n (4 * 3 + n * 3) = 4 + n (12 + 3n) = 4 + n Solving 12 + 3n = 4 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 12 + 3n + -1n = 4 + n + -1n Combine like terms: 3n + -1n = 2n 12 + 2n = 4 + n + -1n Combine like terms: n + -1n = 0 12 + 2n = 4 + 0 12 + 2n = 4 Add '-12' to each side of the equation. 12 + -12 + 2n = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 2n = 4 + -12 2n = 4 + -12 Combine like terms: 4 + -12 = -8 2n = -8 Divide each side by '2'. n = -4 Simplifying n = -4
| 6=6-3a-6a | | x/3+x/7=8/3 | | 2y+y=-24 | | 3/5a-3=6 | | (5-2i)(5+9i)= | | 0.08a=56 | | 4+1/8b=-8 | | 1+0.065= | | 2/7a=4 | | 12=-a/6 | | (-4-6i)(-4+6i)= | | y=-2x^2-5x-2 | | -9=10+a | | z+9=-17 | | 115=37.3x+4.9x^2 | | 6(7)=15(2x+4) | | 0=105+63.19*t-0.5*9.81*t^2 | | 9(x-2)=7x | | 45+180(x-1)=1665 | | 180+45a=1665 | | 14-3*2+4= | | (x+4)/8=(x-2)/6 | | 143x^2-17280x+518400=0 | | 3[6+8(4-1)]= | | 3=3-5s-6s | | x^2+7x=16+x | | 3+2(2-2)= | | 7y+y=-48 | | 4(x-5)-28=-8 | | -10-(-5)+8-3= | | 3+2(a-2)= | | -s+3=-5s+21 |